PENGARUH PENGGUNAAN ERYTHIRNA SUBUMBRANS MERR ( DAUN DADAP SEREP) SEBAGAI ALTERNATIF PENANGANAN BENDUNGAN ASI PADA IBU MENYUSUI - Rahmawati, Dechoni; Dewi Anggraeni, Fatimah (INVOLUSI: Jurnal Ilmu Kebidanan, 2023)
Background: Breast milk dam is a condition commonly experienced by breastfeeding mothers that can cause pain and complaints in the breast. There are several traditional medicines that are believed to help overcome breast milk dams, one of which is Erythrina subumbtans. However, there are still few studies that prove the effectiveness of Erythrina subumbtans in treating breast milk dams in nursing mothers (Amalia, 2019). Research Objective: The purpose of this study was to determine the effect of using Erythrina subumbtans as a traditional medicine to treat breast milk dams in nursing mothers. Research Method: This study will use a pre-post test design with a sample of 20 breastfeeding mothers suffering from breast milk dams. Then, they will be divided into two groups, namely the intervention group that will be given Erythrina subumbtans and the control group that is not given the drug. The data collected will be analyzed using statistical tests with a significance level of 5% The location of this study is in the working area of Puskesmas Sedayu 2, Bantul, Yogyakarta with a sample of 20 respondents and Total Sampling sampling techniques. The data analysis technique used in this study was Wilcoxon. Research Results: There is an influence of the use of Erythirna Subumbrans Merr ( spare dadap leaves) as an alternative to breast milk dam treatment in breastfeeding mothers indicated by a p-value of 0.004 where the p-value is smaller than the significance value with an error rate of 5% (0.05). This shows that there is an effect of using Erythirna subumbrans Merr (spare dadap leaves) as an alternative to breast milk dam treatment in nursing mothers